Effects of Exercise Combined with Finasteride on Hormone and Ovarian Function in Polycystic Ovary Syndrome Rats - Chuyan Wu; Feng Jiang; Ke Wei; Feng Lin; Zhongli Jiang (International Journal of Endocrinology)
Exercise can reduce androgen and insulin levels in polycystic ovary syndrome (PCOS) patients. Finasteride is also presumed to improve the developing follicle environment. Therefore, the aim of this study was to observe the effects of the combination of exercise and finasteride therapy on hormone levels and ovarian morphology in rats with polycystic ovary syndrome. Forty female rats were randomly divided into five groups (n=8 each group): the PCOS sedentary group (P-Sed), PCOS exercise group (P-Ex), PCOS finasteride and sedentary group (P-FSed), and PCOS finasteride and exercise group (P-FEx), and healthy, age-matched rats were used as controls (CO). The results indicated that the levels of FINS in the P-FEx group were significantly lower than those in the P-Sed and P-FSed groups, while the ratio of fasting blood glucose (FBG)/fasting serum levels of insulin (FINS) in the P-FEx group was significantly higher than that in the P-Sed and P-FSed groups. Compared to the P-FEx group, serum levels of TT (total testosterone) in the P-Sed and P-FSed groups were significantly increased. The thickness of the follicular membrane and the number of atresia follicles in the P-FEx and CO groups were significantly lower than those in the P-Sed group, but there was no significant difference between the P-Ex and P-Sed groups. These results show that the combined usage of exercise and finasteride does not alter the effects of exercise on increasing insulin sensitivity and reducing androgen levels. There is also a synergistic effect of exercise and finasteride on the morphology of the ovary, including a reduced number of atresia follicles and thickness of the follicular membrane.